Assessing the Role of the ‘Unity Assumption’ on Multisensory Integration: A Review - Chen, Yi-Chuan; Spence, Charles (Frontiers in Psychology, 2017)
There has been longstanding interest from both experimental psychologists and cognitive neuroscientists in the potential modulatory role of various top-down factors on multisensory integration/perception in humans. One such top-down influence, often referred to in the literature as the ‘unity assumption’, is thought to occur in those situations in which an observer considers that various of the unisensory stimuli that they have been presented with belong to one and the same object or event (Welch & Warren, 1980). Here, we review the possible factors that may lead to the emergence of the unity assumption. We then critically evaluate the evidence concerning the consequences of the unity assumption from studies of the spatial and temporal ventriloquism effects, from the McGurk effect, and from the Colavita visual dominance paradigm. The research that has been published to date using these tasks provides support for the claim that the unity assumption influences multisensory perception under at least a subset of experimental conditions. We then consider whether the notion has been superseded in recent years by the introduction of priors in Bayesian causal inference models of human multisensory perception. We suggest that the prior of common cause (that is, the prior concerning whether the multisensory signals originated from the same source or not) offers the most useful way to quantify the unity assumption as a continuous cognitive variable.